Characteristics Of Children Mother Who Have Preeklamsia In Bulukumba Regency - Kurniati, Ely; Sari, Iramaya (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2017)
Childbirth is an important process for a mother. In the process of childbirth naturally the mother will spend a lot of energy and experience changes both physiologically and psychologically. Data obtained in the 2016 Medical Record total maternity of 1589 there were 132 cases of maternity women who experienced preeclampsia which were divided into 36 cases of mild preeclampsia, 36 cases of severe preeclampsia and 90 cases of eclampsia. The formulation of the problem in this study is